Optimization of the directed energy deposition process parameters to improve throughput for steel-based material - Lim, Joel Choon Wee (Nanyang Technological University, 2023)
In this dissertation, a dimensionless theory is developed for rapid parameter development to study single-track clads. A temperature-based cooling time delay technique was developed to improve the fabrication of thin-walls, which is made by stacking the single track clads on top of one another. This study aims to improve adoption of the directed energy deposition (DED) additive manufacturing process to transform manufacturing companies for industry 4.0. Some challenges lie in the lack of skilled workers for this process, which resulted in a few companies pioneering in this technology, with many others lagging due to long material-process-machine development. DED is a metal additive manufacturing (AM) process that deposits molten metal on metallic surfaces, enabling large part fabrication and part repair. Though it can print on any surfaces, it follows a layer-by-layer approach during the AM process that has to start from a datum plane. Challenges such as unknown optimized parameters required for new materials or melt-down and overheating parts and substrates have plagued development time. This study thus aims to further develop methods in the parameter development and temperature control of the DED process for steel-based materials for industrial projects. The development of such a method targets critical parameters for faster material development, thus indirectly improving the adoption rate, and developing a simple yet effective temperature-based cooling process, which helps fabricate high-aspect-ratio parts. First, the various parameters within the DED system were identified to see the influence on part geometry. Next, a dimensionless theorem was developed for rapid parameter development to study its effect on the microstructure and size of single-track clads. Lastly, a temperature-based cooling system was developed to improve the printing of thin walls. The results identified the key parameters crucial in the DED process and further improved the development speed using a dimensionless theorem. Validation work was carried out successfully with steels of different compositions. Further improvements were made using temperature-based cooling to develop methods for Corrax thin wall fabrications that showed higher strength relative to a normally cooled part. This study contributes to the scientific knowledge regarding applying the dimensionless theorem into the DED process and studies the various microstructure evolution in the fabrication of Corrax thin wall parts. It also simplifies the material-process parameter-machine development process for ease of adoption for the manufacturing industry.